Deletion of Zfp521 rescues the growth plate phenotype in a mouse model of Jansen metaphyseal chondrodysplasia - Seriwatanachai, Dutmanee (Federation of American Societies for Experimental Biology, 2011)
Jansen metaphyseal chondrodysplasia (JMC) is caused by a constitutively activating mutation of the parathyroid hormone (PTH)/PTH-related protein (PTHrP) receptor (PTHR1) and is characterized by widening of the metaphyses, reduction of long bone length, and short stature. A transgenic mouse expressing this mutation under the collagen α1(II) promoter has been generated to investigate the mechanisms responsible for this chondrodysplasia. We recently identified zinc finger protein 521 (Zfp521) as a downstream target gene of PTHrP signaling. Interestingly, loss of Zfp521 from chondrocytes leads to reduced cell proliferation and increased differentiation in the growth plate. Thus, we hypothesized that specifically ablating Zfp521 from Jansen chondrocytes could sufficiently rescue the chondrodysplasia phenotype. Our results show that Zfp521 expression is up-regulated in Jansen mouse growth plate chondrocytes and that PTHR1 is required for Zfp521 expression. Its ablation from Jansen chondrocytes restored normal cell differentiation, thus initiating chondrocyte apoptosis at the chondro-osseous junction, leading to partial rescue of endochondral bone formation shown by proper bone length. This study provides the first genetic evidence that Zfp521 is required downstream of PTHR1 signaling to act on chondrocyte proliferation, differentiation, and cell death.—Seriwatanachai, D., Densmore, M. J., Sato, T., Correa, D., Neff, L., Baron, R., Lanske, B. Deletion of Zfp521 rescues the growth plate phenotype in a mouse model of Jansen metaphyseal chondrodysplasia.